Systematics of organic-walled microfossils from the ca. 780–740 Ma Chuar Group, Grand Canyon, Arizona. (14th September 2016) - Porter, Susannah M.; Riedman, Leigh Anne
Abstract: The ca. 780–740 Ma Chuar Group, Grand Canyon, Arizona, provides an exceptional record of life during the diversification of crown-group eukaryotes, just prior to the first Cryogenian glaciation. We document in detail the assemblage of organic-walled microfossils preserved in fine-grained siliciclastics throughout the unit. In contrast with earlier studies, we primarily used SEM to document fossil morphologies, augmented by transmitted light microscopy, FIB-SEM, and TEM. This resulted in the discovery of new species and the recognition of broad-ranging, intraspecific biological and taphonomic variation in other species. Twenty-two species and five unnamed morphotypes are described, including three new species: Kaibabia gemmulella, Microlepidopalla mira, and Volleyballia dehlerae ; two new combinations: Galerosphaera walcottii and Lanulatisphaera laufeldii ; and 17 previously described forms. The possible colonial green alga Palaeastrum dyptocranum Butterfield in Butterfield, Knoll, and Swett, 1994 and the index fossil Cerebrosphaera globosa (Ogurtsova and Sergeev, 1989) Sergeev and Schopf, 2010 (= C. buickii Butterfield, 1994) are described for the first time from Chuar rocks. Lanulatisphaera laufeldii, a locally abundant and globally widespread species characterized by submicrometer filamentous processes that form a reticulate network, may be a useful marker for the time interval just before the appearance of vase-shaped microfossils (VSMs) ca. 740 Ma. Organic-walled microfossil assemblages decline in diversity upsection, coincident with the appearance of VSMs and intermittent euxinia within the basin. Whether this pattern is due to preservational bias related to greater water depth or the higher TOC of upper Chuar rocks or instead reflects biotic turnover related to the spread of euxinic water masses in the basin is unknown.